2013
DOI: 10.1620/tjem.229.227
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Increase of Body Mass Index is Associated with New-Onset Diabetes Mellitus after Kidney Transplantation

Abstract: New-onset diabetes after transplantation (NODAT) is a serious complication after kidney transplantation. Obesity was widely identified as a modifiable risk factor for NODAT. Body mass index (BMI) is the most frequently used diagnostic indication of obesity, and higher pretransplant BMI has been reported to be an independent risk factor of NODAT. However, the influence of posttransplant increase in BMI on the development of NODAT during outpatient follow-up has not been established. This is a single-centered re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the retrospective study conducted by Tokodai and colleagues on 158 kidney transplant patients, a significant relationship was found between the increase in BMI and the development of NODAT [15]. In our study, univariate analyses revealed that the pre-transplant BMI value was statistically higher in patients who developed NODAT compared to those who did not.…”
supporting
confidence: 54%
“…In the retrospective study conducted by Tokodai and colleagues on 158 kidney transplant patients, a significant relationship was found between the increase in BMI and the development of NODAT [15]. In our study, univariate analyses revealed that the pre-transplant BMI value was statistically higher in patients who developed NODAT compared to those who did not.…”
supporting
confidence: 54%
“…As in the general population, lifestyle modifications are the cornerstone of PLTDM prevention in LT recipients. The positive association between post-transplant BMI increment and risk of subsequent DM [ 107 ] justifies advising weight loss to LT recipients, although this should not be encouraged immediately after surgery to avoid a negative effect on wound healing [ 106 ]. Exercise or an increase in daily life physical activity should also be recommended [ 106 ].…”
Section: Prevention Of Pltdmmentioning
confidence: 99%
“…Several clinical trials have revealed that lifestyle-change interventions were effective in preventing type 2 diabetes mellitus [6,7] and that they may be applicable in NODAT cases too. We previously reported that the posttransplant increase in body mass index and body fat percentage is associated with the development of NODAT [8,9], indicating that lifestyle-change interventions are useful for preventing NODAT.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, all patients who developed NODAT had received tacrolimus-based immunosuppressive treatment [8]. Hence, in this study, we evaluated the predictive power of the pretransplant HbA1c level for the development of NODAT in patients receiving tacrolimus-based immunosuppressive treatment.…”
Section: Introductionmentioning
confidence: 99%